2019
DOI: 10.3390/cells8111423
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signature of Hepatic Fibrosis: From Individual Pathways to Systems Biology

Abstract: Hepatic fibrosis is a major cause of morbidity and mortality worldwide, as it ultimately leads to cirrhosis, which is estimated to affect up to 2% of the global population. Hepatic fibrosis is confirmed by liver biopsy, and the erroneous nature of this technique necessitates the search for noninvasive alternatives. However, current biomarker algorithms for hepatic fibrosis have many limitations. Given that the liver is the largest organ and a major metabolic hub in the body, probing the metabolic signature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 112 publications
0
56
0
Order By: Relevance
“…The greatest both quantity and quality of potential biomarker data has been leveraged using mass spectrometry methodologies. Metabolic pathways associated with hepatic fibrosis, specifically, for carbohydrates, amino acids, and lipids, have been reviewed [118]. In a Japanese study that employed CE-TOFMS and LC-TOFMS, the progression of fibrosis in NAFLD was reported to be associated with increased serum concentrations of several metabolites, among them the sulfates of the three steroids etiocholanolone (a major testosterone metabolite), dehydroepiandrosterone (a precursor of androgens and estrogens) and 16α-hydroxy-dehydroepiandrosterone (a precursor of estriol).…”
Section: Fibrosis and Cirrhosismentioning
confidence: 99%
“…The greatest both quantity and quality of potential biomarker data has been leveraged using mass spectrometry methodologies. Metabolic pathways associated with hepatic fibrosis, specifically, for carbohydrates, amino acids, and lipids, have been reviewed [118]. In a Japanese study that employed CE-TOFMS and LC-TOFMS, the progression of fibrosis in NAFLD was reported to be associated with increased serum concentrations of several metabolites, among them the sulfates of the three steroids etiocholanolone (a major testosterone metabolite), dehydroepiandrosterone (a precursor of androgens and estrogens) and 16α-hydroxy-dehydroepiandrosterone (a precursor of estriol).…”
Section: Fibrosis and Cirrhosismentioning
confidence: 99%
“…Actually, a large number of studies use 'omics' or 'multi-omics' approaches to depict the complex sequence of events during hepatic fibrosis. The recent findings of metabolic alterations relevant to hepatic fibrosis obtained in selected studies were summarized by Chang and Yang [28]. The authors provide comprehensive information about carbohydrate-, amino acid-, and lipid-associated changes during the initiation and progression of fibrotic liver disease obtained in experimental and clinical studies.…”
Section: Integration Of 'Omics' and 'Multit-omics' In Liver Fibrosismentioning
confidence: 99%
“…Metabolomics has found numerous applications in the study of liver functions in health and disease. Among others, these include: Non-invasive biomarker investigations to discriminate between the different stages of progression of NAFLD using non-invasive biofluids (urine and plasma) [3,4]; investigation of mechanisms underlying hepatic disease progression such as acute-on-chronic liver failure using serum metabolic profiling [5] or fibrosis [6]; characterization of the gut microbiota metabotypes in urine of NAFLD patients [4,7]; nutrimetabolomics studies to unravel hepatic pathways dysregulated directly in liver samples upon various nutritional challenges [8,9]; discovery of new metabolic functions for nuclear receptors, that are important regulators of liver physiology using direct hepatic metabolomics or other informative fluids such as urine and bile [10][11][12][13]; identification of patients at risk for idiosyncratic drug-induced liver injury (IDILI) before drug administration, a concept named "pharmaco-metabolomics", that was first demonstrated in urine of animal models [14] and is now extended to human biofluids (urine and serum) [15,16]; study of mechanisms of action for pharmaceutical drugs in urine and fecal samples [17] and environmental contaminants in HepG2 cells and animal biofluids and tissues [18,19].…”
Section: Introductionmentioning
confidence: 99%